Kepuasan Pengunjung Museum Pusat TNI AD Dharma Wiratama Serta Konsep Pengembangannya - Aisha Astriecia (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2018)
Museum Pusat TNI AD Dharma Wiratama, located in Yogyakarta, is managed by TNI. The specialty of this museum lies in the collection of objects, which only displays historical objects associated with the struggle of soldiers in the struggle for RI’s independence. The museum is under the supervision of the Army History Service rather than the Tourism Department, thus the museum does not have admission fees and guide fees for visitors. This is due to the prohibition of collection or fees from Disjarahad. This study aims to analyze and determine the level of visitor satisfaction based on product quality, availability of facilities, and services, development potential, and the problems contained in this museum. Data will be analized to nd some concepts for developing tourism so that, the museum can increase its tourists visit. The research method is descriptive methode and data are analyzed quantitative and qualitative method. Quantitative data was obtained by distributing questionnaires while qualitative data was obtained by conducting interviews as a tool in verifying the questionnaire data. Based on the result of research, it is known that most visitors of Museum Pusat TNI AD Dharma Wiratama are satis ed with product quality and service provided, yet some visitors are unsati ed with its facilities . In addition, this museum has the potential to be developed in the direction of educational tourism history when viewed from the type of tourists and its location. This museum also needs to do promotion to the surrounding schools and universities so that visits to this museum can increase.